THE INFLUENCE OF EDUTAINMENT METHOD ON STUDENT LITERATION ABILITY - Pratiwi Kartika Sari; Achmad Faqih; Roosiganda Elizabeth; Otto Fajarianto; Haiyan Amalia (International Journal of Education, Information Technology, and Others, 2019)
This study aimed to determine the method of learning paikem education on literacy capability to write the beginning of students in the eyes of Indonesian language in grade 2 SDN Pondok Kacang Timur 03. This research is quasi experimental design. This design is a nonequivalent control group design almost together with the pretest-posttest control group design implemented at SDN Pondok Kacang Timur 03 class 2a (30 students) and class 2b (30 students). Data collection used tests and behaviors. The results showed that edutainment learning method had an effect on writing literacy capability in Indonesian class of SDN Pondok Kacang Timur 03. The capability of initial writing literacy in the experimental class get the average score of pretests 75,3 and posttest 82,76. The average score control class the writing capability of pretest 70.5 and posttest 74.23. The result of the calculation of Thitung hypothesis (7,580) is greater than Ttable (2.002) at α = 0.05. Ho have been rejected cannot be paikem edutainment learning method to the literacy capability of writing the beginning of student